HELP ASAP WILL GIVE BRAINLIST IF AN EXPLANATION IS INCLUDED WITH THE STEP BY STEP PROCESS

The functions f and are defined as follows.

g(x) = - 5x - 1;
f(x) = - 2x ^ 3 - 5

Find f(- 3) and g(4) Simplify your answers as much as possible .

Respuesta :

Answer:

f(x)=49

g(x)= -21

Step-by-step explanation:

Let's start with f(-3)

Replace x with -3:

-2(-3)^3-5

Cube -3 (The ^3 is also called cube)

-2(-27) -5

-2 times -27 is 54

54-5 is 49

Now with g(4)

g(4)= -5(4) - 1

-5 times 4 is -20

-20-1 is -21

Hope this helps!